2018
DOI: 10.1130/ges01674.1
|View full text |Cite
|
Sign up to set email alerts
|

Controls on submarine channel-modifying processes identified through morphometric scaling relationships

Abstract: Submarine channels share morphological similarities with rivers, but observations from modern and ancient systems indicate they are formed under processes and controls unique to submarine settings. Morphologic characteristics of channels-e.g., width, depth, slope, and the relationships among them-can constrain interpretations of channel-forming processes. This work uses morphometric scaling relationships extracted from high-resolution seafloor bathymetry to infer connections between morphology and process in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 76 publications
9
63
0
Order By: Relevance
“…The volume of overbank (levee) deposition in runs 1-3 stayed relatively high (>10 L for each run) as sediment supply rate increased, despite the channel being progressively widened and deepened by channel erosion and overbank deposition ( Figures 5B and 6; Figure S8). These growing levees would normally be predicted to progressively confine the flows due to the flows becoming smaller with respect to the channel form (Hodgson et al, 2016;Shumaker et al, 2018). Instead, the levees continued to be overtopped; probably due to flows becoming progressively larger, experiencing more turbulent mixing and decreased grain-size stratification as the sediment supply rate was increased between runs (Rouse, 1939;Kneller and McCaffrey, 1999;de Leeuw et al, 2018a;Eggenhuisen et al, 2019).…”
Section: Slope Channelsmentioning
confidence: 99%
“…The volume of overbank (levee) deposition in runs 1-3 stayed relatively high (>10 L for each run) as sediment supply rate increased, despite the channel being progressively widened and deepened by channel erosion and overbank deposition ( Figures 5B and 6; Figure S8). These growing levees would normally be predicted to progressively confine the flows due to the flows becoming smaller with respect to the channel form (Hodgson et al, 2016;Shumaker et al, 2018). Instead, the levees continued to be overtopped; probably due to flows becoming progressively larger, experiencing more turbulent mixing and decreased grain-size stratification as the sediment supply rate was increased between runs (Rouse, 1939;Kneller and McCaffrey, 1999;de Leeuw et al, 2018a;Eggenhuisen et al, 2019).…”
Section: Slope Channelsmentioning
confidence: 99%
“…As with levee deposits, differentiating axis, off-axis and margin deposits may lead to better constraints on channel-deposit architecture. The event bed correlation distance in channel deposits is less than 300 m (Figure 3), limited by channel dimensions (Konsoer, Zinger, & Parker, 2013;Shumaker et al, 2018).…”
Section: Lateral Event Bed Continuity By Depositional Environment: mentioning
confidence: 99%
“…In this case, we can speculate that if the levees along the flanks of the structure are formed before significant deposition has occurred downslope along the axis, then these levees could focus the flow, promoting further levee formation downslope, allowing a fully leveed channel to form at arbitrary distances from the canyon mouth. This would further imply that the radial expansion of the channel near the canyon mouth would be much less evident than in the Garcia‐Parker case discussed above, and levee development downstream might lead to the relatively stable channel width seen in observations (Shumaker et al, ). However, without direct evidence regarding the characteristic erosion law in natural systems, this can only remain a speculation.…”
Section: Levee Formationmentioning
confidence: 91%
“…Leveed channels are found in submarine fans not only near submarine canyon outlets, but also at considerable distances downslope; a comprehensive and recent review of a variety of systems is found in Shumaker et al (). Clearly, there must be a generic mechanism promoting the formation of leveed channels well away from the expanding flow directly downstream of the canyon mouth, which is modeled by our similarity solution.…”
Section: Levee Formationmentioning
confidence: 99%
See 1 more Smart Citation